Advantages and disadvantages of high power ultrasound application in the dairy industry - Mislav Muža; Verica Batur; Marija Badanjak; Zoran Herceg; Vesna Lelas; Anet Režek Jambrak (Mljekarstvo)
Preservation of food with thermal sterilisation is usually the most common way nowadays. Besides the positive aim of preservation regarding microorganisms’ reduction, elevated temperature in processing simultaneously causes serious changes in nutritive and organoleptical properties of food. Loss of food quality is related to structure and texture deformations, modification of macromolecules and creation of new compounds coming from reactions that are catalised with temperature. One of the new non-thermal processes that can in large scale improve different processes in food industry is ultrasound. In the last five years, new applications of high power ultrasound (HPU) include inactivation of enzymes and microorganisms, assistance in membrane processes, improvement of dairy product texture, improvement of functional properties of proteins etc. High power ultrasound application is used in emulsification and milk homogenization, but in these processes the most important thing is to monitor possible negative effect like oxidation of fats, inactivation of valuable enzymes and denaturation of proteins. Controled and optimized application of ultrasound demands application of specific ultrasound frequency and optimal treatment time. Treatments should be performed at lower temperatures to avoid negative side effects on treated materials.